Alcohol consumption patterns among riverside populations in an Amazonian region of Brazil (Research, Society and Development, 2024)
Alcohol consumption has been attributed to different meanings and contexts over the years. Studying this behavior is important due to the impact this substance can have on social levels and the development of diseases with significant implications for public health. Focusing on the riverside population reveals difficulties in accessing health education, making them vulnerable to the risk of abusive alcohol and drug use.  This study aimed to analyze the relationship between alcohol exposure and dependence among riverside dwellers of the Bailique Archipelago (AP) and to correlate the observed consumption patterns with their sociodemographic characteristics. The study was a retrospective, descriptive survey conducted in 2020, using a questionnaire with socioeconomic variables along with the AUDIT - Alcohol Use Disorders test. The results demonstrated that the most vulnerable population for abusive use are men, of black ethnicity, married, and with children. Regarding economic variables, those with lower income and fewer years of education showed a higher risk of addiction. Religion emerged as a protective factor against abusive use. Ultimately, it is evident that the harmful use of alcohol results in health, economic, and social losses for individuals. Therefore, health education is recommended to reduce the risks of abusive consumption in this vulnerable population.